“I Didn’t Understand Why it had to be a Woman” Realities of Ghanaian Women in Engineering - Anita Bans-Akutey (goodwood publishing, 2026)
Purpose: This study examines the lived realities of Ghanaian women in engineering (GWIE) within the broader context of persistent gender disparities in science, technology, engineering, and mathematics (STEM). Research Methodology: This study adopts a qualitative design grounded in a phenomenological perspective and guided by social constructivism to capture participants lived experiences. A maximum variation sampling technique was employed to select 20 female engineers to ensure diversity across disciplines and career stages. Data were generated through in-depth interviews and observations and subsequently analyzed using thematic analysis to identify recurring patterns and meanings. Results: The findings revealed that many GWIE experienced unplanned career shifts, often undertaken without consultation. Their educational and professional pathways are marked by versatility and adaptability, reflecting the need to adjust to constrained opportunities in the job market. Participants operate in work environments characterized by entrenched gender biases and infrastructural inadequacies, which limit their professional growth. Nevertheless, GWIE demonstrate strong intrinsic motivation, driven by their passion for engineering and commitment to contributing meaningfully to society. Conclusions: The study concludes that the professional experiences are shaped by a complex interplay of individual resilience, family support, and systemic gendered constraints within engineering institutions. While personal motivation sustains women’s engagement in the field, institutional practices continue to reproduce inequities that hinder their career advancement. Limitations: The reliance on self-reported experiences may be influenced by subjective interpretations Contributions: This study contributes to the limited empirical literature on women in engineering in Ghana by providing context-specific insights into their experiences.